ANALISIS AWAL TAHAP KESEDARAN PENGGUNA TERHADAP PEMBELIAN AYAM HALAL DI SELANGOR: Preliminary Analysis of Consumer Awareness Levels Regarding Halal Chicken Purchases in Selangor - Azhar, Muhammad Afif Zakwan; Zakaria, Zalina; Ahmad Rofaie, Nina Sakinah; Razaly, Muhammad Mazuan (Journal of Shariah Law Research, 2025)
The halal chicken market has gained widespread acceptance among both Muslim and non-Muslim consumers, primarily due to factors such as cleanliness, food safety, and quality assurance. However, empirical studies focusing on Muslim consumers’ awareness of halal chicken purchases remain limited. Although legislative frameworks such as the Trade Descriptions Act 2011, the Consumer Protection Act 1999, and the Food Act 1983 provide a robust legal foundation to safeguard consumers and ensure the authenticity of halal chicken products, the level of consumer awareness in Selangor remains a critical determinant of the effectiveness of these laws in promoting compliance and strengthening the halal ecosystem in Malaysia. Therefore, this study aims to assess the level of awareness among Muslim consumers concerning halal chicken purchases in Selangor, recognized as a key focal point within Malaysia’s halal sector. Data were collected through a pilot questionnaire survey involving 31 respondents, and analysis was conducted using SPSS Version 20. The mean score results indicate that Muslim consumers in Selangor exhibit a good level of awareness when selecting halal chicken, with cleanliness and halal certification as primary considerations. Findings from this pilot study suggest a strong consumer consciousness that can support the broader development of a trustworthy and sustainable halal ecosystem.